Comparison of neutron-physical characteristics of uranium target of assembly "quinta" irradiated by relativistic deuterons and ¹²C nuclei - Artiushenko, M.Yu.; Baldin, A.A.; Berlev, A.I.; Chilap, V.V.; Dalkhajav, O.; Sotnikov, V.V.; Tyutyunnikov, S.I.; Voronko, V.A.; Zhadan, A.A. (Вопросы атомной науки и техники, 2016)
At the present time disposal of spent nuclear fuel and fuel supply problem are two main reasons preventing wide distribution of nuclear power. One of the ways to solve this problem is using Nuclear Relativistic Technologies aimed at forming of maximum hard neutron spectrum in natural or depleted massive uranium targets irradiated by high energy (2…10 GeV) beams of relativistic particles. This paper describes the neutron generation in massive natural uranium target (assembly "QUINTA", mU ~ 500 kg) irradiated by beams of relativistic deuterons and 12C ions with energies of 2 and 4 AGeV at the accelerator Nuclotron (JINR, Dubna). The reactions natU(n,f), ²³⁸U(n,γ), and ⁵⁹Co(n,x) were investigated using activation technique. Comparison of obtained experimental results in dependence on energy of incident beam and type of particles was carried out.